INDIVIDUAL CONSTITUTIONAL COMPLAINT AS AN EFFECTIVE INSTRUMENT OF PROTECTION OF HUMAN RIGHTS AND CONSTITUTIONALISM DEVELOPMENT - Pūraitė-Andrikienė, Dovilė (Teisė, 2015)
This article analyzes some of the theoretical and practical problems of the introduction of individual constitutional complaint. However this work mainly focuses on the solutions for the dilemma between overburdening of the constitutional court and providing an efficient human rights protection system. These issues are analyzed on the basis of different Lithuanian and foreign constitutional law scholarly works, which enable to reveal the widest possible amplitude of approaches to the discussed subject. Specific aspects of introduction of individual constitutional complaint mechanism are analyzed on the basis of experience of foreign countries and generalizing it “Draft study on individual access to constitutional justice” by European Commission for Democracy through Law (Venice Commission). In this article are mainly used historical, comparative, analytical and systematic research methods.This work led to the conclusion, that the essential idea of constitutionalism is the limitation of government to protect human rights and therefore the prevalence of constitutional complaint in Europe reflects an even deeper entrenchment of constitutionalism in this region. The introduction of this institute in national law system would be an important step in the promotion of human rights and the development of constitutionalism in Lithuania. The delay of introduction of constitutional complaint mechanism in the national law system reflects that the trend to contrast constitutionalism and democracy is still evident, as if possibility for the persons to apply to the Constitutional Court would led to the constraints of the will of the majority. However, the modern concept of democracy is no longer associated only with the will of the majority and parliamentary sovereignty, its essence is the balance between majority government and respect for the fundamental rights and freedoms. The balance between the excessive workload of the Constitutional Court and the efficiency of individual access to the constitutional justice, would comply with the normative constitutional complaint model, combined with extension of the possibilities of other persons (for example ombudsman institution) to address the Constitutional Court. The requirement of exhaustion of other legal remedies, time-limits for applications, obligation to be legally represented and other conditions for opening proceedings, which allow rejecting frivolous, repetitive, potentially unsuccessful complaints, could also help to solve the problem of overburdened Constitutional Court. In order to make that these conditions would not unduly restrict the possibility of a person to defend their violated rights, there should be some exceptions.